A STUDY ON THE OCULAR MANIFESTATIONS OF ROAD TRAFFIC ACCIDENT CASES ATTENDING GOVERNMENT REGIONAL EYE HOSPITAL - KRISHNA, RAJIV (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Road traffic accidents (RTA) are increasing day by day because of rapid increase in India’s population resulting in a greater number of people commuting. Added to this due to busy schedules of both employees and students there is enormous rise in RTA. The aim of the study is to analyze various ocular manifestations of eye injuries due to RTA attending an eye hospital. Methods: This study is cross-sectional study. 144 patients attending Regional Eye Hospital from January 2022 to June 2022 with various RTA were examined clinically by noting Best corrected visual acuity, Anterior segment, posterior segment examination, and Radiological imaging. Data were analyzed using Microsoft excel 2019 software. Results: In this study, nearly 50% of subjects were in 16–35 years age group. Two-thirds in the study group were males. People from all walks of lives were involved in RTA. About 35% of the study group were commuting in a two-wheeler. More than 50% of the patients presented between 24 and 72 h after RTA. Majority of patients presented with some visual loss. Almost all the patients presented with some form of eyelids involvement like bruising or edema. Most common anterior segment finding was subconjunctival hemorrhage. Conclusion: Ocular injuries due to RTA cause significant morbidity in certain individuals. Frequent commuters are more prone for RTA. Strictly abiding traffic rules and wearing protective gears will significantly reduce ocular trauma.